UV-B irradiation promotes anthocyanin biosynthesis in the leaves of Lycium ruthenicum Murray - Chen, Shengrong; Xu, Yunzhang; Zhao, Weimin; Shi, Guomin; Wang, Shuai; He, Tao (PeerJ (San Francisco, CA), 2024)
Anthocyanins are the most valuable pigments in Lycium ruthenicum Murray ( L. ruthenicum ). Although ultraviolet-B (UV-B) irradiation is a key environmental factor influencing anthocyanin biosynthesis in L. ruthenicum , the deep molecular mechanism remains unclear. Herein, we examined the changes in the total anthocyanin content and transcriptomic characteristics of L. ruthenicum leaves following UV-B irradiation treatment. The results showed a twofold increase in anthocyanin content in the leaves of L. ruthenicum after the treatment. The transcriptome analysis showed that the expression of 24 structural genes identified in the anthocyanin synthesis pathway was up-regulated. In particular, F3’H (Unigene0009145) and C4H (Unigene0046607) exhibit notable up-regulation, suggesting their potential roles in anthocyanin synthesis. Protein interaction network results revealed that MYB1 (Unigene0047706) had the highest connectivity, followed by bHLH (Unigene0014085). Additionally, UVR8 (Unigene0067978) and COP1 (Unigene0008780) were found to be highly involved in UV-B signal transduction. These findings provide new insights into the genetic and biochemical mechanisms that regulate anthocyanin production, and could guide agricultural practices to reduce environmental impacts and improve crop yield and quality.